Growth and Instability in Pine Rosin Production, Export and Import In India - Prasad, Niranjan (Indian Forester, 2026)
This study examines the growth and instability in India’s production, export, and import of pine rosin from 2003–04 to 2023–24. Analysis reveals a severe decline in domestic resin production, particularly in Himachal Pradesh and Uttarakhand, with an overall annual growth rate of –7.326% between 2007–08 and 2019–20. This drop is attributed to ecological stressors, unsustainable tapping practices, socio-economic shifts, and policy constraints. As a result, India’s export volumes collapsed by over 86%, becoming highly unstable and marginal, while unit export values rose significantly. Conversely, imports grew steadily at 3.124% per annum, reaching 42,542 tonnes in 2023–24, with over 75% sourced from Indonesia, highlighting heavy import dependence. Instability indices confirm volatile exports but stable imports, underscoring supply-side vulnerabilities. The paper concludes with a forward-looking estimate suggesting that tapping just 5% of India’s Pinus roxburghii trees could meet domestic demand, save approximately 47.82 million in imports, and generate significant rural employment. Urgent policy interventions are recommended to revitalize sustainable domestic production and reduce external reliance.